AODTH-008 Proximity extension assay based proteins show immune cell specificity and can diagnose and predict outcomes in inflammatory bowel diseases: ibd character study. (17th June 2017) - Kalla, R; Adams, AT; Vatn, S; Bergemalm, D; Ricanek, P; Lindstrom, JC; Ocklind, A; Nordberg, N; Kennedy, NA; Ventham, N; Vatn, MH; Soderholm, JD; et al.
Abstract : Introduction: Proximity extension assays (PEA) allows multiprotein profiling and utilises the specificity of antibody proximity and the sensitivity of polymerase chain reaction to detect proteins of interests. As part of IBD Character, we performed high-throughput prospective case-control serum profiling to identify proteins that can predict Inflammatory Bowel Disease (IBD) and its disease course. Method: Serum profiling was performed in newly diagnosed IBD and Non-IBD cases using PEA panels (Olink Proteomics) from 6 centres in Europe. Phenotypic data were obtained for all patients and follow up outcome data were captured for the Edinburgh and Oslo IBD cohorts. Treatment escalation was defined as the need for surgery and/or biologic therapies after initial induction of remission. Statistical analysis was performed using R. Results: Protein profiles were available in 635 patients (152 CD, 159 UC, 26 IBD-U, 298 non-IBD). 61 protein markers were significantly associated with IBD including MMP12 (Holm-adjusted p=4.1×10–26). Mapping top markers to cell-specific FANTOM 5 [1], several differentially expressed proteins originate from innate and adaptive immune cells such as dendritic cells. 5 proteins differentiate UC from CD including MMP-12 (p=4.6×10–4) Follow up data were available for 206 patients of which 49 patients required treatment escalation. The data were randomly split into a testing (n=130) and a validation cohort (n=76). Using multivariable analyses with age, sex and follow up time as covariates, 9 proteins survived Holm adjustment and 8 of these proteins remained signficant in the validation cohort. 1000 iterations of unsupervised linear discriminant consensus clustering were performed using 7 randomly selected top proteins and identified 2 patients groups that had significantly different disease courses(Image):logrank p=2.2×10–10, HR 5.6 (2.0–15.6); outperforming conventional biomarkers in predicting treatment escalation (hsCRP >4 mg/L, HR 3.2 (1.7–5.8), p=0.0003 and Alb <36 g/L, HR 2.7 (1.4–5.2), p=0.0004). Conclusion: We have identified immune cell-specific PEA-based serum proteins that can diagnose IBD and predict disease course. These data demonstrate the translational potential of a PEA based technology in IBD Reference: . FANTOM Consortium(2014), A promoter level mammalian expression atlas, Nature2014, 507:462–70 Disclosure of Interest: R. Kalla: None Declared, A Adams Conflict with: EC FP7, S Vatn: None Declared, D Bergemalm: None Declared, P Ricanek: None Declared, J Lindstrom: None Declared, A Ocklind Conflict with: Olink is an SME within IBD Character, N Nordberg Conflict with: Olink is an SME within IBD Character, N Kennedy: None Declared, N Ventham: None Declared, M Vatn: None Declared, J Soderholm: None Declared, M Pierik: None Declared, L Torkvist: None Declared, F Gomollon: None Declared, J Jahnsen: None Declared, J Halfvarson: None Declared, J Satsangi: None Declared